An R Package for Value at Risk and Expected Shortfall. Issue 9 (20th October 2016) - Chan, Stephen; Nadarajah, Saralees; Afuecheta, Emmanuel
Abstract : Value at risk and expected shortfall are the two most popular measures of financial risk. But the available R packages for their computation are limited. Here, we introduce an R contributed package written by the authors. It computes the two measures for over 100 parametric distributions, including all commonly known distributions. We expect that the R package could be useful to researchers and to the financial community.